Numerical modelling of cooperative and noncooperative three transboundary pollution problems under learning by doing in Three Gorges Reservoir Area - Lu, Zuliang; Li, Lin; Cao, Longzhou; Yang, Yin (Mathematical Modelling and Analysis, 2020)
In this paper, we investigate cooperative and noncooperative three transboundary pollution problems in Three Gorges Reservoir Area where emission permits trading and abatement costs under learning by doing are considered. The abatement cost depends on two key factors: the level of pollution abatement and the experience of using pollution abatement technology. We use the optimal control theory to study the optimal emission paths and the optimal pollution abatement strategies under cooperative and noncooperative three transboundary pollution problems, respectively. By using the actual economic data of Wanzhou District, Kaizhou District and Yunyang County, we obtain the abatement level and the pollution stock of cooperative and noncooperative three transboundary pollution problems based on the four order Runge-Kutta method. We also discuss the influence of the change of parameter for the abatement level and the pollution stock.